Attitudes and beliefs towards implementation of nurse prescribing among general nurses and nurse specialists in China: A cross‐sectional survey study - Dong‐Lan Ling; Jiale Hu; Mei‐Yun Zhong; Wan‐Ting Li; Hong‐Jing Yu (Wiley, 2021)
Abstract Aims To investigate the attitudes and beliefs towards the implementation of nurse prescribing among general nurses and nurse specialists. Design A cross‐sectional survey among general nurses and nurse specialists was conducted in seven provinces and one autonomous region in mainland China using convenience sampling method. Methods The attitudes and beliefs towards nurse prescribing were assessed using the Nurse Attitudes and Beliefs towards Nurse prescribing scale, of which Cronbach's coefficient was 0.902, retest reliability was 0.808. Respondents from eight hospitals across the country were employed to complete an online questionnaire. Results Nurse specialists (n = 399) had statistically significantly more favourable intentions towards nurse prescribing than general nurses (n = 415; 105.64 ± 12.83 vs. 96.39 ± 13.16; p < .001). The years of clinical work experience, professional title, education degree were positively correlated with general nurses' and nurse specialists' attitudes and beliefs towards nurse prescribing (p < .05). Among nurse specialists, the variety of specialties and whether they work in nurse‐led clinics on an outpatient basis have positively influence on their intentions towards nurse prescribing (p < .05).